Research on factors affecting organizational structure, operating mechanism and audit quality: An empirical study in Vietnam - Hai, Phan Thanh; Tu, Chuc Anh; Toan, Le Duc (Journal of Business Economics and Management, 2019)
This research aims to determine factors affecting and the level of their influence on organizational structure, operating mechanism and audit quality in the Vietnamese market. In this paper, the methodology used by the authors is mixed method. Combination of the qualitative research method and the quantitative research method on the basis of meta-analysis and synthesis of existing information from various sources and results of interviews carried out in early 2018 using a questionnaire for 270 auditors who now work at audit firms in Vietnam. The results of the research showed that factors affecting the operating mechanism of audit firms include the legal system, quality control and internal corporate governance. Factors affecting the audit quality are the organizational structure and the operating mechanism of audit firms. Among these factors, the operating mechanism has the greatest impact on and plays a decisive role in the audit quality. In addition, the research showed that factors affecting the organizational structure of audit firms in Vietnam are unobvious.